Spanish consensus document on diagnosis, stabilisation and treatment of pediatric multisystem inflammatory syndrome related to SARS-CoV-2 (SIM-PedS) - Alberto García-Salido (Anales de Pediatría (English Edition), 2021)
A new paediatric multisystem inflammatory syndrome, linked to SARS-CoV-2 (MIS-Paed), has been described. The clinical picture is variable and is associated with an active or recent infection due to SARS-CoV-2. A review of the existing literature by a multidisciplinary group of paediatric specialists is presented in this document. Later, they make recommendations on the stabilisation, diagnosis, and treatment of this syndrome. Resumen: Se ha descrito un nuevo síndrome inflamatorio multisistémico pediátrico vinculado a SARS-CoV-2 (SIM-PedS). Este cuadro presenta una expresividad clínica variable y se asocia a infección activa o reciente por SARS-CoV-2. En este documento se revisa la literatura existente por parte de un grupo multidisciplinar de especialistas pediátricos. Posteriormente se realizan recomendaciones sobre estabilización, diagnóstico y tratamiento de este síndrome.